Six-Week Preparation Period and its Effects on Transformation Movement Speed with Football Players Under 16 - Jovan Gardašević; Duško Bjelica; Ivan Vasiljević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
The main aim of the research was to identify a level of quantitative changes of the movement speed with fifteen years old football players under the influence of the programmed football training of a six weeks preparation period. The training programme covered forty-four training units. The research was made on a sample of 120 cadet level football players. To estimate the movement speed three tests have been used: foot tapping on the wall, sprint to 20m high start and sprint to 60m high start. In the area of comparative statistics, we used discriminant parametric procedure t-test for big paired samples. Can be concluded that there are statistically significant differences in all three variables to estimate the movement speed. This confirmed the hypothesis that the expected significant positive quantitative changes of basic-motor abilities influenced by the proposed model of training in preparation period with fifteen years old football players. The authors were guided by the fact that this kind of training program in preparation period, where dominates the situational model training is very effective in terms of raising the movement speed level with fifteen years old. The obtained results can be directed towards innovation plans and programs in the preparation period, and the adaptation of the same needs of the respective population.